Chlorination of Conjugated Nitroalkenes with PhICl2 and SO2Cl2 for the Synthesis of α-Chloronitroalkenes - Fadeeva, Anastasia A.; Ioffe, Sema L.; Tabolin, Andrey A. (Synthesis, 2020)
Chlorination of conjugated nitroalkenes with iodobenzene dichloride or sulfuryl chloride to give target α-chloronitroalkenes in good yields is described. Details of the procedure depend on the donating ability of the nitroalkene substituents. The activity of the described chlorinating agents increases in order ‘PhICl2/Py’ < ‘SO2Cl2’ < ‘SO2Cl2/HCl’ with the former producing the best yields for highly donating substrates and the latter for non-activated groups. An autocatalytic role of hydrogen chloride and the chemoselectivity of chlorination were also demonstrated.
Keywords: nitroalkenes; halogenation; chlorination; nitro compounds; chemoselectivity